Prevalence of ocular motor nerve palsy among diabetic patients in Erbil city, Iraq - Kadhim Ahmed, Hiba; Hussein Alwan, Eman (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: The burden of morbidity and mortality caused by the complications of acute and chronic hyperglycemia is rising along with the prevalence of diabetes mellitus in the world. About 50% of diabetic patients will eventually develop neuropathy. In particular, the abducens, oculomotor, and trochlear nerves, which supply the extraocular muscles, are affected by the most common diabetic cranial mononeuropathies. This study is to determine the prevalence, risk factors, and main treatment options for ocular motor nerve palsy in diabetes individuals. Methods: During the period from 1st of August 2021 to 31st of March 2022, a cross-sectional study was conducted in the Ophthalmology Department/ Rizgary Teaching Hospital and Erbil Teaching Hospital. A convenient sample of 500 patients who were diagnosed with diabetes was enrolled in the current study. Results: Out of the 500 patients, 6 (1.2%) had oculomotor nerve palsy, of them, 2 (33.3%) had ptosis, 4 (66.6%) had diplopia, and 2 (33.3%) had pain. Trochlear nerve palsy was diagnosed in 2 (0.4%) of the patients. Of them, 2 (100%) had diplopia. Only one patient was diagnosed with abducent nerve palsy and presented with diplopia. Diabetic retinopathy was diagnosed in 31.3%. Conclusion: The prevalence of ocular motor nerve palsy was low among diabetic patients in the current study but it was higher than recorded in other studies. Many factors including occupation, smoking, alcohol, hypertension, hyperlipidemia, cerebrovascular disease, Aspirin use, duration of diabetes, and presence of diabetic retinopathy can affect the prevalence of ocular motor nerve palsy.